Critical Psychology and Career Development: Unpacking the Adjust-Challenge Dilemma - Prilleltensky, Issac; Stead, G. (2012)
Adjusting to the world of work or challenging it is a dilemma that career counselors and helpers encounter daily. Counselors and clients may opt for one of the following choices: (a) adjust to, and challenge the system, at the same time, (b) adjust to the system but do not challenge it, (c) challenge the system but do not adjust to it, and (d) neither adjust to the system nor challenge it. These four scenarios are analyzed from the perspective of critical psychology and psychopolitical validity. A model depicting the various consequences of each choice for power relations, social justice, and the well-being of people, organizations, communities, and the environment is introduced. The model can guide practitioners in discerning the consequences of their actions and those of their clients.